Heart Failure Study: Profile of Heart Failure Admissions in Medical Intensive Care Unit
Heart failure (HF) is a major cause of morbidity and mortality all over the world. In developed countries because of aging population and increased prevalence of coronary artery disease, heart failure has attained epidemic proportions, whereas, in developing countries like Nepal, rheumatic heart dissease is still the commonest cause of HF admission in medical intensive care unit (MICU). A retrospective study analysing registered data of HF admissions in MICU of Shahid Gangalal National Heart Centre (SGNHC) from August 2002 to OCtober 2008. Among these, 1771 patients were admitted for management of HF and were included in this study. Mean age was 45.07 Å